2020
DOI: 10.3389/fbioe.2020.00660
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Multi-Enzymes on Support Materials for Efficient Biocatalysis

Abstract: Multi-enzyme biocatalysis is an important technology to produce many valuable chemicals in the industry. Different strategies for the construction of multi-enzyme systems have been reported. In particular, immobilization of multi-enzymes on the support materials has been proved to be one of the most efficient approaches, which can increase the enzymatic activity via substrate channeling and improve the stability and reusability of enzymes. A general overview of the characteristics of support materials and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 114 publications
0
77
0
Order By: Relevance
“…The extensive reviews on different nanosupports and enzyme immobilization strategies are recently reported. [21,23,63,64,65]…”
Section: Nanoreactors Performing Cascade Reactionsmentioning
confidence: 99%
“…The extensive reviews on different nanosupports and enzyme immobilization strategies are recently reported. [21,23,63,64,65]…”
Section: Nanoreactors Performing Cascade Reactionsmentioning
confidence: 99%
“…In this section, we will highlight recent improvements in enzyme immobilization methods with respect to flow biocatalysis. Both carrier-free and carrier-bound strategies are well known in the literature, [130][131][132][133][134] and will be briefly discussed and summarized below. In this context, the recently published review article by Bolivar et al is worth mentioning describing the characterization and evaluation of immobilized enzymes for applications in continuous flow reactors in an excellent way.…”
Section: Fundamentals Of Enzyme Immobilization With Respect To Continmentioning
confidence: 99%
“…The need to reduce operational costs of complex cascade reactions for industrial use has driven efforts aimed at increasing the operational performance of biocatalysts and overcoming costs associated with expensive co-factors [15]. Enzyme immobilization is a common strategy for improving the economics of a biocatalytic process by increasing enzyme stability, performance and allowing for biocatalyst reuse and easier product recovery [16][17][18][19][20]. While traditional methods of absorption or attachment to matrices or surfaces work well for the immobilization of one or two enzymes, the co-immobilization of multiple cascade enzymes is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Sequestration, encapsulation, protein-protein interactions, and surface attachments increase enzyme stability and activity, prevent degradation and increase reaction efficiency by creating local co-factor and substrate pools. Inspired by these mechanisms, new types of co-immobilization strategies are therefore increasingly developed that emphasize spatial organization via diverse scaffolding and compartmentalization approaches [18,[21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%